Peran Akuntansi Manajemen Dalam Pengambilan Keputusan Taktis Pada Perusahaan Manufaktur - Purwanti, Purwanti; Siti Nurhayati (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Tactical decision-making is a critical aspect of operational management in manufacturing companies, requiring accurate and relevant information. Management accounting plays a key role in providing cost data, variance analysis, and other financial insights to support this process. This study aims to explore how management accounting systems assist managers in making short-term decisions, such as pricing, production capacity management, and cost control. Based on case studies and a literature review, the findings indicate that the effective implementation of management accounting enhances operational efficiency and supports more strategic decision-making.